A study on fetomaternal outcome of hypertensive disorders of pregnancy - Preet, Adarsh; Anand, Ashok R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Hypertensive disorders of pregnancy are one of the most common medical disorders seen during pregnancy. Early diagnosis of hypertensive disorders in pregnancy by regular antenatal checkup can help in proper management, thus decreasing the maternal and fetal complications related it. Ensuring timely and effective care requires appropriate use of evidence-based clinical and nonclinical interventions, strengthened health infrastructure, and motivated and competent health care providers. The objective of this study was to study the feto-maternal outcome of hypertensive disorders of pregnancy and complications related to them. Methods: A study was conducted in the department of obstetrics and gynecology at JJ Group of hospitals, Mumbai, India for a duration of 18 months from January 2020 to June 2021. This study had a sample size of 500 antenatal patients. Necessary information such as their detailed clinical, and obstetric history, clinical examination, investigations was noted. Results: In our study, the incidence of hypertensive disorders of pregnancy was 10.2%, being most common in age group of 21-25 years (45.1%) and Primigravida patients (47.1%). The most common type of hypertensive disorder in our study was non severe preeclampsia with incidence of 74.50%. The most common complication was oligohydramnios (11.76%), followed by preterm delivery (9.80%) and IUGR (9.80%). The most common drug used in the management of hypertensive disorder was lobetalol. Most common neonatal complication in PIH group was low birth weight, followed by fetal distress (19.6%), prematurity (9.8%) and IUGR (9.8%). Conclusions: Hypertensive disorders of pregnancy are one of the medical conditions affecting pregnancy. Hypertensive disorders of pregnancy are more prevalent in younger and nulliparous mothers. Early diagnosis and appropriate timely management of hypertensive disorders in pregnant women can prevent the maternal and fetal complications and improve the outcome of pregnancy. These women should be monitored carefully to prevent maternal morbidity and mortality.